Mixed-methods research in wellbeing and health - Locke, Rachel, 1967-; Lees, Amanda (London : Routledge, 2021)
Mixed-Methods Research in Wellbeing and Health brings together nine examples of high-quality research into wellbeing and health using a range of mixed methods. Research that employs mixed methods can yield robust data that is both more reliable and valid than that arising from a single-method approach. Mixed-methods research is a vital component in responding to recent changes to the more complex needs of an increasingly diverse society and its health sector. This book covers how mixed-methods research can be designed creatively and applied sensitively in the context of wellbeing and health research. The editors have included a set of bespoke questions for reflection at the end of each chapter. The expert editorial commentary highlights the benefits and methodological challenges of mixed-methods research as well as thinking points' for researchers as they plan and carry out mixed-methods research on wellbeing and health topics. Within a holistic view of wellbeing and health, the mixed-methods research designs are applied appropriately in both practice and community settings. The research can be shaped by pragmatism and the actual needs of a study rather than purely theoretical considerations. This practical book makes high-quality, mixed-methods research design and execution guidance readily accessible to health-care practitioners and researchers working in the fields of health, social care and wellbeing services and to undergraduate and postgraduate students in courses in research and health-care studies, as well as health management.
Introduction 1. Methodological Issues in Researching Everyday Music Therapy Practice Dr Claire Flower 2. Using a Mix of Qualitative Methods to Investigate Vulnerability in the Medical Profession Dr Rachel Locke, Dr Jane Bell and Dr Samantha Scallan 3. Qualitative Methods to Optimise Design and Conduct of Randomised Controlled Trials with Clinical Populations Dr Andrew Mitchelmore 4. Mixed Methods and Wellbeing: Issues Emerging from Multiple Studies into Mentoring for Doctors Professor Alison Steven and Dr Gemma Wilson 5. Mixing Methods and Data: Exploring Health and Wellbeing on a Social Scale Dr David Harrison, Asta Medisauskaite and Dr Eliot L. Rees 6. Community-participatory Investigation of the Health-environment-wellbeing nexus of WaSH in Eural Eswatini Dr Michelle R. Brear 7. Using Mixed and Multi-modal Methods in Psychological Research with Young People Dr Debra Gray, Dr Rachel Manning and Shokraneh Oftadeh-Moghadam 8. A Multimethods Approach to Defining a Strategy for Engaging Vulnerable Families in Research Dr Amanda Lees and Dr Kit Tapson 9. Mixed Methods in Community-based Health and Wellbeing Practices Professor Geoffrey Meads Conclusion: Developing Mixed Methods Research Practice in Wellbeing and Health
Keywords: Public health -- Research -- Methodology; Well-being -- Research -- Methodology; Mixed methods research; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research